Student’s attendance system using fingerprint technology / Farahanum Masruni - Masruni, Farahanum (2006)
This project is about designing and developing a system, Student’s Attendance System (SAS) that will record the attendance of student in Fakulti Teknologi Maklumat & Sains Kuantitatif (FTMSK). SAS using fingerprint technology to authenticate every student by using their fingerprint in order to get an accurate record. The fingerprint technology is cheaper and easy to implement compared to other biometrics technology. The fingerprint only authenticates the validated student. SAS with the fingerprint features can make the system secure because no student can record their attendance except to be authenticated by the system. Besides provides security, this new system provides efficiency to both lecturers and students. SAS focused on the developing system using SDLC as the methodology. This system using personal computer that is run under Windows 2000 platform and develop using apache, PHP and MySQL. This system uses the questionnaire method in order to analyze the user acceptance among respondents. In conclusion, this is important to provide the reliable and efficient record.